2000
DOI: 10.1074/jbc.275.15.10745
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activities of Vasostatin-1, the N-terminal Fragment of Chromogranin A

Abstract: Vasostatin-1, the natural N-terminal 1-76 chromogranin A (CGA)-derived fragment in bovine sequence, has been purified from chromaffin secretory granules and identified by sequencing and matrix-assisted laser desorption time-of-flight mass spectrometry. This peptide, which displays antibacterial activity against Gram-positive bacteria at micromolar concentrations, is also able to kill a large variety of filamentous fungi and yeast cells in the 1-10 M range. We have found that the C-terminal moiety of vasostatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
141
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 67 publications
(126 reference statements)
5
141
0
1
Order By: Relevance
“…CgA exists in various endocrine organs and its secretion is regulated by the SAM system 15,16) . In vitro experiments have also demonstrated that CgA exhibits antifungal and antibacterial properties 17,18) . Salivary CgA concentration increases rapidly under psychosomatic stress 19) , although the response of CgA to exercise is yet to be determined.…”
Section: ⅰ.Introductionmentioning
confidence: 99%
“…CgA exists in various endocrine organs and its secretion is regulated by the SAM system 15,16) . In vitro experiments have also demonstrated that CgA exhibits antifungal and antibacterial properties 17,18) . Salivary CgA concentration increases rapidly under psychosomatic stress 19) , although the response of CgA to exercise is yet to be determined.…”
Section: ⅰ.Introductionmentioning
confidence: 99%
“…Previous studies showed that a peptide encompassing residues 47-66, called chromofungin, could interact with lipids and penetrate into the cytoplasm of fungi (27,28). In addition, it has been shown that chromofungin can inhibit calcineurin, a calmodulin-activated phosphatase (28).…”
Section: -51 (Rilsi)mentioning
confidence: 99%
“…Thus, chromaffin cells possess in their microenvironment all of the components necessary for exerting a tightly regulated proteolytic cleavage of CgA. Plasminogen activation and CgA processing may not be limited to the surface of chromaffin cells, because many other neuroendocrine and non-neuroendocrine cells can express these molecules (3,27). Given the well recognized importance of fibroblasts and plasminogen activation in tissue invasion, remodeling, and repair (49 -52), the interplay between CgA and the plasminogen/plasmin system could provide a novel mechanism for regulating fibroblast adhesion and function in physiopathological conditions characterized by CgA hyperproduction, such as neuroendocrine tumors and chronic heart failure.…”
Section: -51 (Rilsi)mentioning
confidence: 99%
See 2 more Smart Citations